Autoestima y Estrategias de Afrontamiento en pacientes con cáncer de mama. - Amaguaya Macas, Paola Alexandra (2023)
Breast cancer is a worldwide health problem in which women are treated using several treatments causing secondary effects in their physical and psychological appearance, this may cause a strong impact on patients’ self-esteem due to female identity is closely related to the breasts. This research has shown that women who presented low self-esteem face emotional difficulties in choosing adequate coping strategies, on the other hand women who present high self-esteem have a better quality of life and use more adequate coping strategies. A bibliographic and documentary methodology was used in this research. Sixty scientific papers were examined, these were organized in scientific articles and post grade thesis which were collected from several databases such as Elsevier, Scielo, Dialnet, Redalyc, Proquest, Taylor and Francis and Google academic, published between the years 2013-2023. A non-probabilistic sample based on inclusion and exclusion criteria of 50 articles was selected based on selection criteria. The CRF-QS method was used to ensure methodological quality. The results showed that the selfesteem of breast cancer patients is linked to the choice of coping strategies, to identify the levels and types of coping strategies were taken into account sociodemographic data, and to identify the types of coping strategies.